Evidence-Based Scar Management: How to Improve Results with Technique and Technology. (September 2016) - Khansa, Ibrahim; Harrison, Bridget; Janis, Jeffrey E.
Abstract : Background: Scars represent the visible sequelae of trauma, injury, burn, or surgery. They may induce distress in the patient because of their aesthetically unpleasant appearance, especially if they are excessively raised, depressed, wide, or erythematous. They may also cause the patient symptoms of pain, tightness, and pruritus. Numerous products are marketed for scar prevention or improvement, but their efficacy is unclear. Methods: A literature review of high-level studies analyzing methods to prevent or improve hypertrophic scars, keloids, and striae distensae was performed. The evidence from these articles was analyzed to generate recommendations. Each intervention's effectiveness at preventing or reducing scars was rated as none, low, or high, depending on the strength of the evidence for that intervention. Results: For the prevention of hypertrophic scars, silicone, tension reduction, and wound edge eversion seem to have high efficacy, whereas onion extract, pulsed-dye laser, pressure garments, and scar massage have low efficacy. For the treatment of existing hypertrophic scars, silicone, pulsed-dye laser, CO2 laser, corticosteroids, 5-fluorouracil, bleomycin, and scar massage have high efficacy, whereas onion extract and fat grafting seem to have low efficacy. For keloid scars, effective adjuncts to excision include corticosteroids, mitomycin C, bleomycin, and radiation therapy. No intervention seems to have significant efficacy in the prevention or treatment of striae distensae. Conclusion: Although scars can never be completely eliminated in an adult, this article presents the most commonly used, evidence-based methods to improve the quality and symptoms of hypertrophic scars, as well as keloid scars and striae distensae.